Хімічне конструювання та дослідження властивостей магнітокерованих адсорбентів для екстракції нуклеїнових кислот - Semko, L. S.; Hutornyy, S. V.; Storozhuk, L. P.; Dzyubenko, L. S.; Abramov, N. V.; Gorbyk, P. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
In accordance with our proposed model of the structure magnetically layered adsorbents for adsorption of nucleic acids (Fe3O4/SiO2/polymetacryloxypropylsiloksane/polyacrylamide), a method for their synthesis was developed. Layers of adsorbent were identified by the help of XRD and FTIR spectroscopy. The DTA and thermogravimetry data gave the opportunity to estimate the thermal stability and processes of thermodestruction for layers of the heated adsorbent and maid possible to determine the Curie and Neel temperatures for magnetite. The magnetic properties of the adsorbents were investigated. A relationship between the structure of nanocomposites Fe3O4/SiO2, Fe3O4/SiO2/ polymetacryloxypropylsiloksane, Fe3O4/SiO2/polymetacryloxypropylsiloksane/polyacrylamide and their magnetic characteristics was found. The obtained adsorbent was shown extract DNA from the solution totally.